Utilization of Organic Waste in Compost Fertilizer Production: Implications for Sustainable Agriculture and Nutrient Management - Bremaghani , Ade (Law and Economics, 2024)
This research explores the utilization of organic waste in compost fertilizer production, aiming to elucidate its implications for sustainable agriculture, organic waste management, and environmental stewardship. Through a comprehensive analysis of compost quality indicators, microbial dynamics, and nutrient management strategies, the study investigates the efficacy, feasibility, and implications of integrating organic waste into composting processes. Key findings reveal significant variations in nutrient content, pH levels, maturity, and microbial activity among compost samples derived from diverse organic waste feedstocks. The nutrient-rich composition, pH stability, and biologically active nature of compost fertilizer offer promising alternatives to conventional chemical fertilizers, with implications for soil health improvement, crop productivity enhancement, and environmental sustainability. Moreover, the research underscores broader implications for waste management practices, circular economy principles, and agroecological resilience. By valorizing organic waste through composting, stakeholders can contribute to waste diversion, greenhouse gas mitigation, and resource conservation, while promoting community engagement and economic development. The integration of composting practices with sustainable agriculture initiatives offers synergistic opportunities for enhancing ecosystem services, climate resilience, and food security.